THE STRUGGLE OF THE MAGICIAN DIELA IN THE NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM BY DIAN PURNOMO - Wahyu Nugraha; Aris Badara; Irianto Ibrahim (CASA CENDEKIA MEDIA, 2025)
This study is motivated by the importance of women's awareness in shaping their existence, including the existence of female characters in novels. This study aims to identify forms of marginalization against women and the struggle of the character Magi Diela in fighting marginalization as a manifestation of women's existence in the novel Perempuan yang Menangis Kepada Bulan Hitam (Women Who Cry to the Black Moon) by Dian Puromo. The theory of female existence refers to the feminist theory of a French female expert named Simone de Beauvoir. The research subject used is the novel Perempuan yang Menangis Kepada Bulan Hitam (Women Who Cry to the Black Moon) by Dian Puromo. The object of this research is the forms of marginalization and female existence based on Simone de Beauvoir's existentialist feminist theory. This research is descriptive qualitative research. The data analysis technique used in this research is the Miles and Huberman data analysis model, which consists of three stages, namely data reduction, data presentation, conclusion drawing, and verification. The results of the study show the presence of marginalization of women in the novel Perempuan yang Menangis Kepada Bulan Hitam by Dian Puromo in the form of women always being viewed as weak, which leads to various forms of violence against women. The form of resistance found in the character Magi Diela as a manifestation of self-existence is the struggle for intellectuality, refusing to be objectified, and determining her own destiny.